2021
DOI: 10.20944/preprints202107.0510.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Improving the Accuracy of Gridded Population Estimates in Cities and Slums to Monitor SDG 11: Evidence from a Simulation Study in Namibia

Abstract: People living in slums and other deprived areas in low- and middle-income country (LMIC) cities are under-represented in censuses, and subsequently in "top-down" gridded population estimates. Modelled gridded population data are a unique source of disaggregated population information to calculate local development indicators such as the Sustainable Development Goals (SDGs). This study evaluates if, and how, WorldPop-Global (WPG) -Unconstrained and -Constrained “top-down” datasets might be i… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 23 publications
(29 reference statements)
0
1
0
Order By: Relevance
“…The web mapping services include not only the footprints of buildings, but also point-of-information data such as addresses, building usage, building type, and building functionality, as well as other information about the buildings. In this context, several prior research [4,30,[33][34][35][36][37][38] identified building Data 2022, 7, 45 3 of 23 types using web mapping services such as OpenStreetMap (OSM) [39,40], Google maps, Gaode Maps, and Baidu Maps [4,35]. For instance, ref.…”
Section: Introductionmentioning
confidence: 99%
“…The web mapping services include not only the footprints of buildings, but also point-of-information data such as addresses, building usage, building type, and building functionality, as well as other information about the buildings. In this context, several prior research [4,30,[33][34][35][36][37][38] identified building Data 2022, 7, 45 3 of 23 types using web mapping services such as OpenStreetMap (OSM) [39,40], Google maps, Gaode Maps, and Baidu Maps [4,35]. For instance, ref.…”
Section: Introductionmentioning
confidence: 99%